(untitled) (Security Dialogues, 2025)
This research examines the unconventional tactics and strategies inherent in special forces, focusing on methods such as diversion, sabotage, assassination, and subversion. We analyse how these strategies affect national and international security using a multidisciplinary approach that incorporates theoretical frameworks from criminology, political science, and security studies. The article reveals the complex interactions between special tactics and broader security dynamics, highlighting how they can simultaneously serve as instruments to achieve political goals and raise significant ethical and legal dilemmas. The research results provide deeper insight into the mechanisms of special operations and their consequences, offering practical guidelines for shaping effective responses to security challenges in the modern world. This article is not only theoretically relevant but also has direct practical implications for security policies and strategies at the global level.